Երրորդաբանական բնորոշումները եւ աստուածաշնչեան դրուագները Ս. Ներսէս Շնորհալու «Բան հաւատոյ» ստեղծագործութեան մէջ - Աւագեան, Նարեկ Տ. վարդապետ (Մայր Աթոռոյ Սրբոյ Էջմիածնի)
Стихотворный труд Св. Нерсеса Шнорали «Слово о вере» — это 36-строфный гимн с армянским алфавитным акростихом, где каждая строфа состоит из 4 строк. В каждом из первых девяти строф описывается Святая Троица, а с 10 по 36 строфы относятся к следующим эпизодам Библии: сотворение, изгнание из рая, потоп, вавилонское столпотворение. The poetical work of St. Nerses the Graceful entitled “Words of Faith” is an acrostic of thirty six verses composed according to the Armenian alphabet, and each verse consists of four lines. Each of the first nine verses characterizes the Holy Trinity and the rest refers to the following biblical episodes: creation, expel from the paradise, flood, building of the Tower of Babel. Separate verses are dedicated to patriarchs Abraham and Jacob, as well as to Prophet Moses. Prophets of the Old Testament are mentioned collectively; then Christ’s Incarnation and salvation is spoken about.
Keywords: Religion; Literature